Penguatan peran keluarga dalam pencegahan masalah gizi balita melalui Positive Deviance di Kabupaten Deli Serdang - Tanjung, Nadya Ulfa (Talenta Publisher, 2024)
Early childhood is one groups with the highest risk of nutritional problems because in this phase the first rapid growth process takes place. The impact of malnutrition includes impaired growth and development, decreased productivity and resistance to disease, impaired brain structure and function, and behavioral changes in the next life. Nutritional problems are directly caused by food intake and history of infection, while the availability and utilization of health services, family parenting, food availability and household sanitation will indirectly increase the risk. The research was conducted using a mixed method approach. In the early stages of the study, nutritional status measurements of all toddlers will be carried out followed by extracting information on intake history and other related information needed. Furthermore, information will be extracted from informants to provide answers related to the social situation of the community and individual experiences. Toddlers with normal nutritional status are nurtured with a Positive deviance pattern in the form of feeding, parenting, hygiene, and good health service utilization. Expanding the knowledge and ability of mothers in implementing of effective parenting for toddlers is important to improve the attitude and behavior of mothers to obtain good nutritional status and prevent early childhood from experiencing growth failure conditions such as stunting.